NON-SURGICAL TREATMENTS OF LYMPHEDEMA OF THE LOWER LIMBS - Rosas, Francisca (2019)
Background: LLL is characterized by protein-rich interstitial fluid accumulation due to lymphatic system insufficiency, resulting in progressive non-pitting edema. Primary and secondary lymphedema are distinguished by the absence or presence of an external trigging factor, respectively. Diagnosis is based on clinical examination combined with imaging modalities. The non-surgical approach of LLL is based on preventive measures, lifestyle interventions and life-long compression modalities, aiming to reducethe edema congestion and to improve patient quality of life.Objectives: The present literature review aims to compile current scientific knowledge on the various domains of the non-surgical treatments of LLL.Methods: Search was performed in PubMed database, using the following medical subjects heading (MeSH) terms: “lymphedema”, “lower limbs” and “medical treatment”. Research and review articles indexed in the last 10 years and written in English language were selected. Animal experimentation works and single case-reports were excluded. Other materials searched comprised reference books in the area of Vascular Surgery, namely Rutherford Vascular Surgery — 9th Edition, 2018. Development: The non-surgical treatment of LLL is characterized by a multifaceted approach, including mechanical reduction of limb swelling, alternative medical devices and pharmacological therapy. Complex decongestive therapy is recognized as the standard of treatment and its compression modalities include drainage massages, pneumatic compression, bandaging systems, compression garments and physical exercise. Compression therapies differ in the degree and time of pressure applied and can be performed by healthcare professionals or by the patient himself. The duration of treatment stages varies and it mayinclude hospital and outpatient regimens. Positive treatment outcomes include increased skin elasticity, limb volume reduction, pain relief, increased functional capacity and improved quality of life.Conclusions: Compression modalities have been shown to be effective in reducing limb volume, increasing tissue elasticity and improving the physical, psychological and aesthetic aspects of patient life. However, sustained volume reductions depend mostly on patient diligence. Intensive and outpatients approaches do not compromise treatment efficacy and high pressures therapies are effective and well tolerated. Current lymphedema non-surgical treatment lacks long-term results and urges more effective therapeutic alternatives.